Thunberg's Way in the Climate Debate: Making Sense of Climate Action and Actors, Constructing Environmental Citizenship. Issue 4 (19th May 2022) - Fonseca, Alice; Castro, Paula
ABSTRACT: Considering the impact of Greta Thunberg on the contemporary climate debate and activism, this article seeks to understand the meaning-making patterns that structure her message. An interdisciplinary approach is used, integrating socio-psychological perspectives with the environmental citizenship literature, to develop a systematic analysis of 25 of Thunberg's public speeches, exploring: (1) the oppositional meaning-categories ( themata ) she chooses as relevant for making sense of climate change and her positions regarding them; (2) how she values or devalues different climate actors; (3) the type of environmental citizenship she constructs. Findings show that the themata structuring Thunberg's message – notably action/inaction – are accompanied by a counter-stereotypical devaluation of "leaders" as cold and incompetent and valuation of "youth" and "public" as competent. Her emphasis on collective responsibilities over individual rights and call on citizens to publicly demand transformative climate action also signal how Thunberg constructs an environmental citizenship aligned with "strong sustainability".